A Girth Designed to Avoid Peak Pressure Locations Increases Limb Protraction and Flexion During Flight. (9th September 2013) - Murray, R.; Guire, R.; Fisher, M.; Fairfax, V.
Abstract : Introduction: Girths are frequently blamed for veterinary and performance problems, but research into girth/horse interaction is sparse. Aims: To 1) determine location of peak pressure under a range of girths; 2) compare horse gait between horse's standard girth and a girth designed to avoid detected peak pressure locations. Methods: Part 1: Following validation procedures, a calibrated pressure mat placed under the girth of 10 horses was used to determine location of peak pressures. Based on these results, a girth was designed to avoid locations of peak pressure (Girth A). Part 2: Twenty elite horses/riders were included for study based on selection for British Equestrian Federation (BEF) World Class Programme Performance Squad, with no lameness or performance problem. Horses were ridden in Girth A and their standard girth (Girth S) in a crossover design, with riders blinded to girth type. Pressure mat data was acquired from under the girths. High‐speed video was captured in trot, using standard anatomical marker placement. Forelimb and hindlimb protraction, maximal carpal and tarsal flexion during flight were determined. Good repeatability was confirmed. Results: In standard girths, peak pressures were located over musculature behind elbow. Pressure mat results revealed maximum forces with Girth S were 22% (left) and 14% (right) greater than Girth A, and peak pressures were 76% (left) and 98% (right) greater (P<0.01 for all). On gait evaluation, girth A was associated with 6–11% greater forelimb protraction, 10–20% greater hindlimb protraction, 4% greater carpal flexion, and 3% greater tarsal flexion than Girth S (P<0.01 for all). Conclusions and practical significance: Peak pressures were located where horses are reported to develop pressure sores. Girth A reduced peak pressures under the girth, and improved limb protraction and carpal/tarsal flexion, which may reflect improved posture and comfort. Ethical animal research: This study involved informed consent of the riders/owners of horses used in the study.Sources of funding: UK Sport lottery funding for the BEF World Class Programme, Fairfax Saddles.Competing interests: Vanessa Fairfax is employed by Fairfax Saddles.